Simulasi Pola Operasi Waduk Batutegi, Provinsi Lampung : Simulation of Batutegi Reservoir Operation Pattern, Lampung Province - Swastika, Dian; Wulandari, Dyah Ari; Sriyana, Ignatius (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2022)
Batutegi Reservoir is a multi-purpose reservoir that is used to increase the water supply to the Argoguruh Weir to expand the irrigation area in the Sekampung Irrigation System. Batutegi Reservoir supplies the water demand not only for irrigation, covering an area of 66.573 Ha, but also for hydroelectric power generation (hydropower) of 2 x 14 MW and the raw water supply of 2.250lt/s. The operational curves of the Batutegi Reservoir were prepared in 2017, aiming to control the water release to ensure the planned demand is fulfilled. However, the reservoir operation curves must be reviewed at least once every 5 (five) years to comply with the changes in reservoir conditions and the development of its benefits/functions. The study aimed to determine the reservoir reliability by updating the reservoir operation curves in 3 conditions; wet year, normal year, and dry year using the SOR (Standart Operating Release) simulation method according to the inflow and outflow during the mid-month period. Results showed that in the wet year, normal year, and dry year, the reservoir reliability in supplying water for irrigation, raw water, and hydropower is satisfactory in each period. In conclusion, although some simulation periods showed the final RSL (Reservoir Water Levels) of the reservoir are below the upper limit of the operation curves, they are still above MOL (Minimum Operation Level) hydropower level meaning all supply for irrigation, raw water, and hydropower can be 100% fulfilled.